Effects of Biochar and Compost on Growth and Yield of Sweet Pepper under a Partial Root-Zone Drying Irrigation System - Omran, Abdulrasoul Al-; Ibrahim, Alaa; Alharbi, Abdulaziz (Canadian Journal of Agriculture and Crops, 2019)
This study was carried out to assess the effects of compost (CO2 and CO4), biochar (B2 and B4), and biochar–compost mixture (Mix2 and Mix4), at rates of 2% and 4%, on the yield and water use efficiency (WUE) of sweet pepper under greenhouse conditions. Pepper plants were irrigated by partial root-zone drying (PRD) using two levels of water irrigation, 75% from evapotranspiration (ETc) (PRD75%ETc) and 50% from ETc (PRD50%ETc). The objectives of this study were to evaluate the distribution of soil water, salinity, and root system of bell pepper and changes in the WUE of bell pepper due to the PRD technique. The contour lines showed that the salinity was improved by adding biochar, compost, and their combination because the moisture content of the amended soil was the highest compared to that of the control (untreated soil). The WUE of pepper under PRD75%ETc was 7.5, 6.1, 8.7, 6.69, 9.5, and 7.7 kg m-3 for B4, B2, CO4, CO2, Mix4, and Mix2, respectively. The WUE under PRD50%ETc was 9.8, 8.2, 10.2, 8.5, 11.7, and 10.1 kg m-3 for B4, B2, CO4, CO2, Mix4, and Mix2, respectively. The irrigation water saved was 35% and 57% under PRD75%ETc and PRD50%ETc, respectively.